Traços de personalidade sombria e a teoria do comportamento planejado no julgamento e tomada de decisão do auditor - Araujo, Lorena Costa de Oliveira (2022)
In recent years, the Judgment and Decision-Making (JDM) process has aroused the interest of researchers in the accounting area and has merited empirical investigation, seeking to understand the way individuals process information and the factors that influence judgment. and decision-making in the field of auditing. One of the factors that has been gaining prominence in the literature is the dark personality traits that influence how individuals interact with their environment, collect and process information and make decisions. Thus, based on the Theory of Planned Behavior, this thesis proposes that the auditor's judgment and decisionmaking is a function of attitude, subjective norms and perceived behavioral control. However, it is assumed that this relationship is negatively moderated by the auditors' dark personality traits (dark tetrad). Thus, the objective of this research is to analyze the effect of dark personality traits (dark tetrad) on the relationship between the conditioning factors of the Theory of Planned Behavior - attitudes, subjective norms and perceived behavioral control - and the judgment and decision making of auditors. For this purpose, a descriptive study was carried out, through survey research, of a quantitative nature, with the population of Brazilian independent auditors registered at the Instituto dos Auditores Independentes do Brasil - IBRACON, and a final sample of 311 respondents whose questionnaires presented valid answers. To achieve the objectives of this thesis, statistical treatments were used: descriptive statistics, non-parametric Kruskal-Wallis test, Partial Least Squares Modeling of Structural Equations (PLS–SEM) and Partial Least Squares Multigroup Analysis (PLS-MGA). The results indicate that, within the scope of the audit, the three conditioning factors established in the Theory of Planned Behavior – attitudes, subjective norms and perceived behavioral control – have a positive and significant effect on the auditors' judgment and decision-making regarding materiality, continuity and key audit matters. Regarding the control variables, the results indicate that the auditor's gender and the type of audit firm to which he belongs have an effect on the auditor's judgment and decisionmaking. Regarding the moderation of personality traits, the results showed that this thesis is accepted only for the conditioning factors Subjective norms and Perceived behavioral control, which showed a negative influence of dark personality traits on the auditor's judgment and decision-making, validating that auditors with high dark personality traits (Dark Tetrad) manifest tendencies towards insensitivity, impulsiveness, manipulation, criminality, grandiosity, enjoyment of cruelty and bad conduct, suggesting that auditors with these traits ignore ethical codes (subjective norms), and use their knowledge (perceived behavioral control) to make judgments and decision-making to achieve their goals, thus impairing the quality of their judgment and decision-making. With regard to the conditioning factor Attitude – professional skepticism, the dark personality traits positively influenced their relationship with judgment and decision-making, rejecting what was advocated in this thesis. Furthermore, the results indicate that moderation by personality traits is analogous to the dark tetrad construct for Machiavellianism, narcissism and psychopathy traits, an exception identified for sadism that did not moderate the relationship attitude, perceived behavioral control and judgment and decision making, demonstrating the differentiated influence of this personality trait in the audit environment. Among the contributions of this research, we highlight the empirical validation of the predictive power of the Theory of Planned Behavior in the behavioral determination of auditors' judgment and decision-making, considering personality traits, and the creation of a model that encompasses, in addition to the attitude , subjective norm and perceived behavioral control, personality traits of the auditor, which proved to be a moderating construct of the relationship with effects on judgment and decision making.